A Self‐Regulated Interface toward Highly Reversible Aqueous Zinc Batteries. Issue 9 (15th January 2022) - Han, Daliang; Wang, Zhenxing; Lu, Haotian; Li, Huan; Cui, Changjun; Zhang, Zhicheng; Sun, Rui; Geng, Chuannan; Liang, Qinghua; Guo, Xiaoxia; Mo, Yanbing; Zhi, Xing; et al.
Abstract: Aqueous zinc batteries, that demonstrate high safety and low cost, are considered promising candidates for large‐scale energy storage. However, Zn anodes suffer from rapid performance deterioration due to the severe Zn dendrite growth and side reactions. Herein, with a low‐cost ammonium acetate (NH4 OAc) additive, a self‐regulated Zn/electrolyte interface is built to address these problems. The NH4 + induces a dynamic electrostatic shielding layer around the abrupt Zn protuberance to make the Zn deposition uniform, and the OAc − acts as an interfacial pH buffer to suppress the proton‐induced side reactions and the precipitation of insoluble by‐products. As a result, in the electrolyte with the NH4 OAc additive, Zn anodes exhibit a long cycling stability of 3500 h at 1 mA cm −2, an impressive cumulative areal capacity of 5000 mAh cm −2  at 10 mA cm −2, and a high Coulombic efficiency of ≈ 99.7%. A prototype full cell coupled with a NH4 V4 O10  cathode performs much better in terms of capacity retention than the additive‐free case. The findings pave the way for developing practical Zn batteries. Abstract : A self‐regulated interface is built using a dual‐functional ammonium acetate additive to address zinc dendrite growth and proton‐induced side reactions simultaneously, thus enabling an Zn anode with long cycling stability of 3500 h, an impressive cumulative areal capacity of 5000 mAh cm −2  at 10 mA cm −2, and a high Coulombic efficiency of 99.7%.